2017
DOI: 10.1200/jco.2017.73.7338
|View full text |Cite
|
Sign up to set email alerts
|

Modernizing Clinical Trial Eligibility Criteria: Recommendations of the American Society of Clinical Oncology–Friends of Cancer Research HIV Working Group

Abstract: Purpose People with HIV are living longer as a result of effective antiretroviral therapy. Cancer has become a leading cause of morbidity and mortality in this patient population. However, studies of novel cancer therapeutics have historically excluded patients with HIV. Critical review of eligibility criteria related to HIV is required to accelerate development of and access to effective therapeutics for HIV-infected patients with cancer and make studies more generalizable to this patient population. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
98
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(104 citation statements)
references
References 17 publications
6
98
0
Order By: Relevance
“…We did not observe increased incidence of infection‐related deaths among HIV patients who received rituximab. These relevant findings reinforce the need to enroll HIV patients in prospective clinical trials and carefully consider the use of rituximab on the front‐line treatment of HIV‐related DLBCL patients.…”
Section: Discussionsupporting
confidence: 55%
“…We did not observe increased incidence of infection‐related deaths among HIV patients who received rituximab. These relevant findings reinforce the need to enroll HIV patients in prospective clinical trials and carefully consider the use of rituximab on the front‐line treatment of HIV‐related DLBCL patients.…”
Section: Discussionsupporting
confidence: 55%
“…2,3 There are several potential concerns that distinguish an HIV-infected patient from a patient without HIV being considered for CAR T-cell therapy. [12][13][14] Although much remains to be learned regarding CAR T-cell therapy in patients with refractory hematologic malignancies, with or without HIV infection, the cases presented herein demonstrate that patients with chemotherapy-refractory, highgrade, B-cell lymphoma can successfully undergo autologous CAR T-cell manufacturing, and subsequently can safely tolerate CAR T-cell therapy and achieve a durable complete remission. We do know that, in general, patients with HIV-associated malignancies can tolerate full-dose cancer therapy as appropriate for their HIV-uninfected counterparts.…”
Section: Discussionmentioning
confidence: 89%
“…FDA oncology staff are in a unique position to articulate important research questions based on review work across cancer types and product classes and have access to oncology clinical trial data submitted by multiple sponsors for meta‐analyses and data to study patterns of regulatory submissions over time . Recent FDA oncology publications have addressed a variety of regulatory science topics, including the following: Describing new methods to design clinical trials for regulatory submissions such as master protocols , patient‐reported outcome tools , expansion cohorts , and tumor‐agnostic drug development . Exploring clinical trial endpoints . Investigating approaches to ensure that clinical trials are representative of the general population such as expanding eligibility criteria , understanding representation of diverse populations , and using real world data (e.g., electronic health record data) to inform regulatory actions . …”
Section: Introductionmentioning
confidence: 99%